An Investigation into the Tunnel-Soil-Pipeline Interaction by In Situ Measured Settlements of the Pipelines - Xinggao Li; Ting Wang; Yi Yang (Advances in Civil Engineering)
Response of buried pipeline to tunnelling is of great concern in the subway construction. It is of paramount importance but difficult to estimate the influence of tunnelling on adjacent pipelines because of the complex tunnel-soil-pipeline interaction. The technique of in situ measured settlements of buried pipelines remains the standard approach for understanding this interaction and addressing the issue. The Huangzhuang station of the Beijing Subway is located in a densely populated area, with many buried pipelines in the close proximity; the shallow tunnelling method of pile-beam-arch (PBA method) was used to excavate the station tunnels; the shallow tunnelling of the station tunnels inevitably causes settlements of the ground surface and the buried pipelines. Direct monitoring of the pipelines by digging holes from the ground surface was performed during the station tunnel construction. In situ measured settlements of the ground surface and the buried pipelines caused by the subway construction were obtained. It is observed from the obtained results that the pipeline settlement development can be divided into four stages that are associated with different construction periods of the PBA method. Sharp increases in the pipeline settlement occurred in the specific stages (stages 2 and 4). It is concluded from comparisons between the pipeline settlement and the ground surface settlement that separation between steel or cast iron pipelines and the soil beneath occurs due to the tunnel construction. And the pipeline settlement is smaller than that of the ground surface. This finding has the practical implication that the ground surface can be monitored instead of the buried pipeline. Using this indirect pipeline monitoring, the pipeline safety can be conservatively evaluated. This study is an example for evaluating the shallow tunnelling-induced effects on adjacent buried pipelines and understanding the tunnel-soil-pipeline interaction under similar conditions.